ENHANCING S45C STEEL FOR THE PRIMARY COMPONENT OF AN AUTOMATIC COUPLER USING QUENCH-TEMPERING TECHNIQUES - Valentino, Jean Mario; Pramono, Agus Sigit; Syaifudin, Achmad; Agustin, Helena Kis; Shalahuddin, Lukman; Windharto, Agus; Sasaki, Katsuhiko (Journal of Applied Engineering Science, 2024)
Coupling links and hooked plates constitute the primary components of automatic couplers in trains, enduring substantial tensile and compressive loads during train connections. This study endeavours to enhance the strength of S45C material through heat treatment techniques. The research commenced with the preparation of JIS S45C tensile test specimens adhering to ASTM E8 standards. The material's chemical composition was validated using an Optical Emission Spectrometer (OES). Six heat treatment variations were employed, including quench oil without tempering (QO), quenching water without tempering (QW), quenching oil tempered at 660°C (QOT660), quenching water tempered at 660°C (QWT660), quenching oil tempered at 550°C (QOT550), quenching water tempered at 550°C (QWT550), alongside untreated conditions (NT) for comparison. The efficacy of heat treatment was evaluated through tensile testing, optical metallographic analysis, and micro-Vickers hardness tests. QO and QW scenarios were excluded from the tensile tests. Results revealed that QWT550 demonstrated the most substantial enhancement in material yield, exhibiting a 115% increase. Moreover, hardness testing indicated superior hardness in QWT550 specimens compared to other tempered variants. The metallographic analysis illustrated the formation of identical and smooth martensitic structures. Overall, the combination of cooling heat treatment and tempering proved sufficient to meet the design requirements of hooked plates and coupling links for automatic couplers.
Keywords: automatic coupler, quench-tempering, S45C, material characterization